IMPLEMENTASI KURIKULUM MERDEKA UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SEKOLAH DASAR NEGERI DOPLANG 02 KECAMATAN BAWEN KABUPATEN SEMARANG - Mei Riskawati; Ngasbun Egar; Ghufron Abdullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Abstract: The Independent Curriculum encourages teachers to design interesting and relevant learning to the needs of students. This requires teachers to have high pedagogical competence. SD Negeri Doplang 02 is one of the elementary schools that has implemented the Independent Curriculum and is accompanied by an increase in the pedagogical competence of its teachers. This study aims to describe and analyze the planning, implementation and evaluation of learning in the implementation of the independent curriculum at SD Negeri Doplang 02, Bawen District, Semarang Regency. The approach used in this study is a qualitative approach. Data collection techniques use interviews, observations, documentation. This study uses two types of triangulation, namely source triangulation and method triangulation to test the validity of the data. The results of the study show that: 1) Planning for the implementation of the independent curriculum has been carried out well by formulating objectives, formulating content, designing learning activities, determining learning resources and determining evaluations. 2) The implementation of the independent curriculum is effective by focusing on six aspects of independent curriculum learning, including conducting initial assessments, providing opportunities for students to participate, differentiated learning, utilizing technology-based learning media, implementing learning reflections, and implementing formative and summative assessments. 3) Evaluation of the implementation of the independent curriculum is carried out systematically with the stages of compiling evaluation objectives, developing instruments, collecting evaluation data, analyzing data, providing feedback, and utilizing evaluation results. 4) The implementation of the independent curriculum has a positive impact on improving teacher pedagogical competence. There was an increase in pedagogical competence of 15.10 or 21%. This increase occurred in the indicators of mastering students from various aspects, designing and organizing educational learning, facilitating the development of student potential, conducting learning evaluations/assessments, and utilizing information and communication technology for learning purposes. Keywords: Implementation, Independent Curriculum, Pedagogical Competence